Investing abroad: Why Indian firms should forge ahead and how the government can help - Priyanka Kher (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2024)
Countries have used outward FDI to benefit their own economies. In the context of evolving global uncertainties and India's development needs, this Perspective argues that it is timely for Indian firms to invest abroad - seeking strategic assets, resources and new markets - and suggests policy measures to support them.
Keywords: 330